Integrating The Tri Hita Karana Philosophy into Sustainable Economic Education: An Analysis of Student Perceptions at Universitas Pendidikan Ganesha - Yani, Ni Luh Sinta; Azis, Maghfirah Sari; Sari, Puji Novita (Proceeding International Conference on Religion, Science and Education, 2026)
Sustainable economic education emphasizes the importance of achieving equilibrium among economic, social, and environmental aspects within the learning process. One local philosophical framework aligned with this principle is the Tri Hita Karana concept, which promotes harmony among humans and God (parahyangan), humans and others (pawongan), and humans and nature (palemahan). Rooted in Balinese cultural wisdom, this philosophy provides an ethical foundation that enriches the moral and ecological perspectives of economic education. This study aims to analyze the perceptions of Economics Education students at Universitas Pendidikan Ganesha (Undiksha) regarding the integration of Tri Hita Karana principles in supporting sustainable economic learning. The research employed a quantitative descriptive method, with data collected through a structured questionnaire distributed to 100 active students in the Economics Education Study Program. Data were analyzed using descriptive statistical techniques, including the calculation of mean scores and percentage levels across the three main dimensions of Tri Hita Karana. The findings reveal that students hold positive perceptions toward the integration of Tri Hita Karana values in sustainable economic education. The parahyangan dimension achieved an average score of 4.31 (86.2%), indicating a strong awareness of spirituality and moral responsibility. The pawongan dimension recorded an average score of 4.25 (85%), reflecting appreciation for social ethics, cooperation, and empathy. The palemahan dimension obtained an average score of 4.18 (83.6%), signifying concern for environmental and resource sustainability. Overall, the integration of Tri Hita Karana’s local wisdom provides a relevant and effective pedagogical approach to advancing sustainable economic education by cultivating ethical, socially responsible, and environmentally conscious learners.